Early magnetic resonance imaging predictors of clinical progression after 48 months in clinically isolated syndrome patients treated with intramuscular interferon β-1a - Uher, T; Horakova, D; Kalincik, T; Bergsland, N; Tyblova, M; Ramasamy, D P; Seidl, Z; Vaneckova, M; Krasensky, J; Havrdova, E; Zivadinov, R (European journal of neurology, 2015)
BACKGROUND AND PURPOSE: Our aim was to identify early imaging surrogate markers of clinical progression in patients after the first demyelinating event suggestive of multiple sclerosis treated with weekly intramuscular interferon β-1a. In a prospective observational study, the predictive role of baseline and 6-month changes in magnetic resonance imaging outcomes was investigated with respect to relapse activity and development of confirmed disability progression in patients after 48 months. METHODS: This study examined 210 patients. Multivariate Cox proportional hazard models were used to analyse predictors of relapse activity and confirmed disability progression after 48 months. RESULTS: Greater T2 lesion volume [hazard ratio (HR) 1.81; P = 0.005] and the presence of contrast-enhancing lesions (HR 2.13; P < 0.001) at baseline were significantly associated with increased cumulative risk of a second clinical attack over 48 months. A greater decrease of the corpus callosum volume (HR 2.74; P = 0.001) and greater lateral ventricle volume enlargement (HR 2.43; P = 0.002) at 6 months relative to baseline were associated with increased cumulative risk of a second clinical attack between months 6 and 48. In addition, increased risk of confirmed disability progression over 48 months in patients with greater lateral ventricle volume enlargement between baseline and 6 months (HR 4.70; P = 0.001) was detected. CONCLUSIONS: A greater T2 lesion volume, the presence of contrast-enhancing lesions at baseline, decrease of corpus callosum volume and lateral ventricle volume enlargement over the first 6 months in patients after the first demyelinating event treated with weekly intramuscular interferon β-1a may assist in identification of patients with the highest risk of a second clinical attack and progression of disability.
Keywords: recidiva; Magnetic Resonance Imaging; predictors; magnetická rezonanční tomografie; Humans; demyelinizační nemoci; MRI; lidé středního věku; Adjuvants, Immunologic; Disease Progression; lesions; adjuvancia imunologická; Female; dospělí; lidé; Biomarkers; clinically isolated syndrome; Adult; Follow-Up Studies; biologické markery; ženské pohlaví; multiple sclerosis; Male; Middle Aged; Demyelinating Diseases; Recurrence; Injections, Intramuscular; progrese nemoci; mužské pohlaví; injekce intramuskulární; brain atrophy; následné studie; Interferon beta-1a; interferon beta 1a